2019
DOI: 10.1155/2019/8623035
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Modelling of Nonlinear Flow Behavior in Single Fractured Granite

Abstract: In this study, the hydromechanical behavior was experimentally investigated by conducting fracture geometry evolution-based gas flow tests on single fractured granite. The traditional fracture roughness value (Rp) of a single surface cannot adequately explain the intrinsic permeability in multiple samples. Instead, the permeability is better explained by aperture distribution, and it is positively correlated with the mean aperture size. The permeability is also affected by a combination of contact area and voi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Singh KK et al [14] studied nonlinear fluid flow in granite under high confining pressure and high inlet pressure. Su et al [15] carried out a flow test on marble fractures under different effective stresses and found nonlinear fluid flow under high confining pressure. Li et al [16] analyzed the nonlinear flow characteristics of methane gas in shale fractures by conducting shale fracture seepage tests under stress loading and unloading paths.…”
Section: Introductionmentioning
confidence: 99%
“…Singh KK et al [14] studied nonlinear fluid flow in granite under high confining pressure and high inlet pressure. Su et al [15] carried out a flow test on marble fractures under different effective stresses and found nonlinear fluid flow under high confining pressure. Li et al [16] analyzed the nonlinear flow characteristics of methane gas in shale fractures by conducting shale fracture seepage tests under stress loading and unloading paths.…”
Section: Introductionmentioning
confidence: 99%
“…In the last century, numerous studies were carried out to understand flow behavior in a rock fracture generated by different rock types including sandstone, limestone, granite, , shale, , and coal using different kind of fluids such as water, gas, and supercritical CO 2 . According to these studies, it was found that the fracture conductivity was controlled by the geometry of the fracture, the flow rate, and the fluid properties.…”
Section: Introductionmentioning
confidence: 99%